Italijanska zasedba slovenskih krajev v novembru 1918 - Žorž, Grega (Zgodovinski časopis, 2016)
The author demonstrates the course of the Italian occupation of the Slovene territory in November 1918, limiting himself to the operation of Italian military units, their organisation and spatial distribution. He highlights the Allies% conditions of the armistice for Austria-Hungary, containing articles on the time frame of the occupation and geographical delimitation of the area. By presenting authentic internal correspondence, which refl ects the attitudes of the offi cers involved, the author aims to offer new and profound insight into the occupation itself. In doing so, he does not discuss the justness of the occupation or the attitude of the Italian army towards the Slovene population, he merely deals with the military perception of the delimitation line. On account of the incident in Vrhnika in 1918 and the related correspondence, the author presents briefl y the existing Slovene historiographical and popular-scientifi c literature on the subject, based on the analysis of numerous sources, the author provides a critical examination of the event
Keywords: 1918; Italian occupation; italijanska okupacija; prva svetovna vojna; Rapallo border; rapalska meja; Vrhnika; western border; World war I; zahodna meja